1983
DOI: 10.1002/pssb.2221160132
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the correlation between the crystal field axis system and the crystallographic axes in chromium‐doped β‐Ga2O3 by EPR

Abstract: The correct relationship is found between the crystal field axes and crystallographic axes in P-Ga,O, b y application of a simplified orientation method. A computer program is set up, which is able to calculate and to plot the angular variation of the resonance field strengths and of the energy levels involved in EPR. In this way, the strange angular dependence of the E P R lines can be explained and the correctness of the stated correlation between the two axis systems can be verified. From the measured reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The errors in Table I arise from the slight sample misalignment, and not from the large linewidth. 20 The solid lines in Figs. The monoclinic term confirms that the local site symmetry of Cr 3ϩ in the ␤-Ga 2 O 3 crystal is monoclinic, rather than orthorhombic.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The errors in Table I arise from the slight sample misalignment, and not from the large linewidth. 20 The solid lines in Figs. The monoclinic term confirms that the local site symmetry of Cr 3ϩ in the ␤-Ga 2 O 3 crystal is monoclinic, rather than orthorhombic.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…A total number of 316 resonance line positions due to the fine structure of Cr 3ϩ in ␤-Ga 2 O 3 recorded in the three crystallographic planes was used for fitting the SH parameters. 20 For orthorhombic symmetry, the principal axes of the g and D tensors should coincide and the resonance fields should all be symmetric about the extrema in the three principal crystallographic planes; this, however, was not the case. In our room temperature experiments, the signs of the ZFS parameters were not determined.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies, which disclosed all 69 Ga and 71 Ga resonances, yielded eight sets of NMR parameters; these eight sets of resonance lines originated from a twin structure. Also, electron paramagnetic resonance (EPR) studies of Cr 3+ [13,14] in b-Ga 2 O 3 single crystals have been reported.…”
Section: Introductionmentioning
confidence: 98%